Evaluation of Cardioprotective Activity of Aqueous and Ethanolic Extract of Bauhinia Variegata in Cacl2 Induced Arrhythmia in Albino Rats - Rajesh Kumar Sharma, Ashish Kumar Sharma, Govind Mohan (Journal of Applied Pharmaceutical Science, 2013)
The aim of present study was to evaluate cardioprotective activity of ethanolic and aqueous extracts of Bauhinia variegata Linn in CaCl2 induced arrhythmia in albino rats.In present study, i.v injection of 5% CaCl2 solution (25 mg/kg b.w.) that induce arrhythmia without causing mortality and heart rates were monitored throughout the study by a lead II electrocardiogram. CaCl2 reduced heart rate and exhibited alteration in the PQRST waves. Arrhythmia induced by CaCl2 in experimental animals, which is confirmed by change in ECG pattern and sodium, potassium and calcium level in plasma. Pretreatment of extracts prevent the CaCl2 induced arrhythmia by virtue of the potent active constituents. Bauhinia variegata Linn. root extracts produced significantly (P
Keywords: Bauhinia variegata Linn., Electro